TGF beta inhibits HGF, FGF7, and FGF10 expression in normal and IPF lung fibroblasts. Issue 16 (28th August 2018) - Correll, Kelly A.; Edeen, Karen E.; Redente, Elizabeth F.; Zemans, Rachel L.; Edelman, Benjamin L.; Danhorn, Thomas; Curran‐Everett, Douglas; Mikels‐Vigdal, Amanda; Mason, Robert J.
Abstract: TGF beta is a multifunctional cytokine that is important in the pathogenesis of pulmonary fibrosis. The ability of TGF beta to stimulate smooth muscle actin and extracellular matrix gene expression in fibroblasts is well established. In this report, we evaluated the effect of TGF beta on the expression of HGF, FGF7 (KGF), and FGF10, important growth and survival factors for the alveolar epithelium. These growth factors are important for maintaining type II cells and for restoration of the epithelium after lung injury. Under conditions of normal serum supplementation or serum withdrawal TGF beta inhibited fibroblast expression of HGF, FGF7, and FGF10. We confirmed these observations with genome wide RNA sequencing of the response of control and IPF fibroblasts to TGF beta. In general, gene expression in IPF fibroblasts was similar to control fibroblasts. Reduced expression of HGF, FGF7, and FGF10 is another means whereby TGF beta impairs epithelial healing and promotes fibrosis after lung injury. Abstract : TGF beta inhibits the important growth factors HGF, FGF7, and FGF10. This inhibition may be a very important component for the development of pulmonary fibrosis. Control and IPF fibroblasts were inhibited similarly.